Electrical and Corrosion Properties of Titanium Aluminum Nitride Thin Films Prepared by Plasma-Enhanced Atomic Layer Deposition. Issue 3 (March 2017) - Yun, Eun-Young; Lee, Woo-Jae; Wang, Qi Min; Kwon, Se-Hun
Abstract : Titanium-aluminum-nitride (TiAlN) films were grown by plasma-enhanced atomic layer deposition (PEALD) on 316L stainless steel at a deposition temperature of 200 °C. A supercycle, consisting of one AlN and ten TiN subcycles, was used to prepare TiAlN films with a chemical composition of Ti0.25 Al0.25 N0.50 . The addition of AlN to TiN resulted in an increased electrical resistivity of TiAlN films of 2800 µΩ cm, compared with 475 µΩ cm of TiN films, mainly due to the high electrical resistivity of AlN and the amorphous structure of TiAlN. However, potentiostatic polarization measurements showed that amorphous TiAlN films exhibited excellent corrosion resistance with a corrosion current density of 0.12 µA/cm 2, about three times higher than that of TiN films, and about 12.5 times higher than that of 316L stainless steel.